2018
DOI: 10.1016/j.cognition.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Inattentional numbness and the influence of task difficulty

Abstract: Research suggests that clearly detectable stimuli can be missed when attention is focused elsewhere, particularly when the observer is engaged in a complex task. Although this phenomenon has been demonstrated in vision and audition, much less is known about the possibility of a similar phenomenon within touch. Across two experiments, we investigated reported awareness of an unexpected tactile event as a function of the difficulty of a concurrent tactile task. Participants were presented with sequences of tacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
2
9
1
Order By: Relevance
“…First, the auditory surprise distractor effects were consistently modest, when present at all. Such smaller effects are consistent with other studies of cross-modal attention distraction [19,31,49,50,60]. Second, there was little evidence of effects in the 1050 ms SOA, either positive or negative.…”
Section: Intelligent Dynamic Schedulingsupporting
confidence: 90%
See 3 more Smart Citations
“…First, the auditory surprise distractor effects were consistently modest, when present at all. Such smaller effects are consistent with other studies of cross-modal attention distraction [19,31,49,50,60]. Second, there was little evidence of effects in the 1050 ms SOA, either positive or negative.…”
Section: Intelligent Dynamic Schedulingsupporting
confidence: 90%
“…Another example is found in the inattentional numbness phenomenon. When one is paying attention to a demanding visual or tactile task, a strong but unexpected vibrotactile stimulus is often not detected [49,50].…”
Section: Attentional Trade-offsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Gomes, Betza, et al (2020) found that tacton detection was lower when participants were standing and walking than when sitting. Instances of tactile change blindness (Lu & Sarter, 2014; Riggs & Sarter, 2016) and “inattentional numbness” have also been reported (Murphy & Dalton, 2016, 2018).…”
Section: Effectiveness Of Vibrotactile Displays With Competing Tasksmentioning
confidence: 98%